Effects of thumbnail sizes on downstream consumer behavior. - Ng, Zhen Hui. (2010)
Downstream outcomes consist of various components that are directly or indirectly affected by the layout of website such as size of thumbnails. This report consists of two studies which will explore and investigate the relationships between these factors. The first study examines the impact of differing thumbnail sizes on consumer consideration set. In view of the limitations faced by previous Applied Research Project (ARP), the second study seeks to improve the ecological validity of testing conditions and results via a field study. Limitations faced by previous studies include difficulty in enhancing the realism of testing conditions and behaviours. By using the concept of an online blog shop, the second study will eliminate a high percentage of human error and at the same time, create a more realistic test environment for the shoppers. Collated results investigate the effect of thumbnail sizes on actual behaviours, namely enquiry and purchases conversion rates. In addition, valuable insights and implications have also been gathered. First of all, results have shown that between search costs components such as scrolling time and image clarity, purchasers place more importance on the latter. Secondly, enquiry decisions were most frequent for extreme thumbnail sizes (size S or XL). Interestingly, it is found that moderate thumbnail size (M) is the least ideal in terms of both purchase and enquiry conversion.